Accuracy of linear measurements around dental implants by means of cone beam computed tomography with different exposure parameters - Bohner, Lauren O L (Dentomaxillofac Radiol, 2017)
OBJECTIVES: The aim of this study was to determine the accuracy of linear measurements around dental implants when using CBCT unit devices presenting different exposure parameters. METHODS: Dental implants (n = 18) were installed in the maxilla of human dry skulls, and images were obtained using two CBCT devices: G1—Care Stream 9300 (70 kVp, 6.3 mA, voxel size 0.18 mm, field of view 8 × 8 cm; Carestream Health, Rochester, NY) and G2—R100 Veraview(®) (75 kVp, 7.0 mA, voxel size 0.125 mm, field of view 8 × 8 cm; J Morita, Irvine, CA). Measurements of bone thickness were performed at three points located (A) in the most apical portion of the implant, (B) 5 mm above the apical point and (C) in the implant platform. Afterwards, values were compared with real measurements obtained by an optical microscopy [control group (CG)]. Data were statistically analyzed with the significance level of p ≤ 0.05. RESULTS: There was no statistical difference for the mean values of bone thickness on Point A (CG: 4.85 ± 2.25 mm, G1: 4.19 ± 1.68 mm, G2: 4.15 ± 1.75 mm), Point B (CG: 1.50 ± 0.84 mm, G1: 1.61 ± 1.27 mm; G2: 1.68 ± 0.82 mm) and Point C (CG: 1.78 ± 1.33 mm, G1: 1.80 ± 1.09 mm; G2: 1.64 ± 1.11 mm). G1 and G2 differed in bone thickness by approximately 0.76 mm for Point A, 0.36 mm for Point B and 0.08 mm for Point C. A lower intraclass variability was identified for CG (Point A = 0.20 ± 0.25; Point B = 0.15 ± 0.20; Point C = 0.06 ± 0.05 mm) in comparison with G1 (Point A = 0.56 ± 0.52; Point B = 0.48 ± 0.50; Point C = 0.47 ± 0.56 mm) and G2 (Point A = 0.57 ± 0.51; Point B = 0.46 ± 0.46; Point C = 0.36 ± 0.31 mm). CONCLUSIONS: CBCT devices showed acceptable accuracy for linear measurements around dental implants, despite the exposure parameters used.